2020
DOI: 10.1186/s13052-020-00862-z
|View full text |Cite|
|
Sign up to set email alerts
|

Probiotics’ efficacy in paediatric diseases: which is the evidence? A critical review on behalf of the Italian Society of Pediatrics

Abstract: During the last decade several paediatric studies have been published with different possible indications for probiotics, leading to a global increase of probiotics’ market. Nevertheless, different study designs, multiple single/combined strains and small sample size still leave many uncertainties regarding their efficacy. In addition, different regulatory and quality control issues make still very difficult the interpretation of the clinical data. The objective of this review is to critically summarise the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 106 publications
(147 reference statements)
0
13
0
Order By: Relevance
“…As a consequence, daily practice differs substantially in different centers, resulting in a discrepancy in administration from 0 to 100% according to over 150 different neonatal intensive care units [ 103 ]. Many trials do not report any adverse event, but some cases of Lactobacillus or Bifidobacterium sepsis have been reported in infants receiving probiotics [ 104 , 105 , 106 , 107 ]. Most affected infants had severe diseases, such as short-bowel syndrome or immunodeficiency [ 103 ].…”
Section: Results: Evidence Of Efficacy Of Probioticsmentioning
confidence: 99%
“…As a consequence, daily practice differs substantially in different centers, resulting in a discrepancy in administration from 0 to 100% according to over 150 different neonatal intensive care units [ 103 ]. Many trials do not report any adverse event, but some cases of Lactobacillus or Bifidobacterium sepsis have been reported in infants receiving probiotics [ 104 , 105 , 106 , 107 ]. Most affected infants had severe diseases, such as short-bowel syndrome or immunodeficiency [ 103 ].…”
Section: Results: Evidence Of Efficacy Of Probioticsmentioning
confidence: 99%
“…A number of strains have been proposed for the management of pediatric FGIDs ( Wojtyniak and Szajewska, 2017 ; Sung et al, 2018 ; Nocerino et al, 2020 ; Savino et al, 2020 ). However, no specific probiotic strains have gained enough clinical evidence to be recommended by experts except for Limosilactobacillus reuteri DSM 17938 but only in breastfed babies subgroup ( Tabbers et al, 2014 ; Guarner et al, 2017 ; Martinelli et al, 2020 ). In addition to the limited clinical support, strains are not always selected based on beneficial mechanisms to counteract pediatric FGIDs pathophysiology but generally tested in different adult and infant conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The use of LGG for the reduction of the duration of diarrhea is supported by convincing evidence [ 9 ]. A review of randomized clinical trials (RCTs) on LGG in the treatment of AGE in children has reported a reduced duration of diarrhea at a daily dose of ≥10 10 CFU or ≤10 10 CFU by approximately 20 hours [ 10 ].…”
Section: Discussionmentioning
confidence: 99%